2020
DOI: 10.1029/2019wr026515
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Scenario Selection on Robustness

Abstract: Multiple plausible future scenarios are being used increasingly in preference to a single deterministic or probabilistic prediction of the future in the long-term planning of water resources systems. These scenarios enable the determination of the robustness of a system-the consideration of performance across a range of plausible futures-and allow an assessment of which possible future system configurations result in a greater level of robustness. There are many approaches to selecting scenarios, and previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 75 publications
4
28
0
Order By: Relevance
“…Furthermore, some conclusions from scenario generation procedures appear consistent across the different case studies evaluated; for instance, the three studies cited above all find that uniformly distributed scenarios result in different robustness scores and vulnerability characterizations than centrally distributed scenarios. However, they differ in terms of the impact they observe on robustness rankings, with Quinn et al (2020) showing a high influence on robustness rankings that is not apparent in McPhail et al (2020) or Reis and Shortridge (2020). This suggests that the degree to which scenario generation methods influence DMDU outcomes is likely to vary on a case-by-case basis, and points toward the need for multiple comparisons that can highlight common patterns and themes.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, some conclusions from scenario generation procedures appear consistent across the different case studies evaluated; for instance, the three studies cited above all find that uniformly distributed scenarios result in different robustness scores and vulnerability characterizations than centrally distributed scenarios. However, they differ in terms of the impact they observe on robustness rankings, with Quinn et al (2020) showing a high influence on robustness rankings that is not apparent in McPhail et al (2020) or Reis and Shortridge (2020). This suggests that the degree to which scenario generation methods influence DMDU outcomes is likely to vary on a case-by-case basis, and points toward the need for multiple comparisons that can highlight common patterns and themes.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…For instance, robustness measures are generally categorized as either satisficing-or regret-based (Herman et al 2015). Within each of these broad categories, there are multiple mathematical definitions for robustness that quantify how a given alternative performs across the ensemble of scenarios evaluated (McPhail et al 2018(McPhail et al , 2020. These mathematical quantifications allow for comparison of different alternatives, but multiple studies have demonstrated that the choice of robustness metric can influence robustness scores (i.e., how robust an individual or group of alternatives appear to be) and rankings (which alternatives appear most robust) (Drouet et al 2015;Giuliani and Castelletti 2016;Kwakkel et al 2016a, b;McPhail et al 2018).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations